2021
DOI: 10.3390/cancers13133280
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Biomarkers and Biological Pathways for Poor Clinical Outcome in Mucinous Colorectal Adenocarcinoma

Abstract: Colorectal cancer (CRC) comprises several histological subtypes, but the influences of the histological subtypes on prognosis remains unclear. We sought to evaluate the prognosis of mucinous adenocarcinoma (MAC), compared to that of traditional adenocarcinoma (TAC). This study used the data of patients diagnosed with CRC between 2004 and 2016, as obtained from the Surveillance, Epidemiology, and End Results database. We established a predictive model for disease-specific survival using conditional survival for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…Ribosomal protein S18(RPS18), also known as HKE3, is a type of ribosomal protein which has been supposed to an unfavorable predictor in several cancers including breast cancer (BC) 23 and colorectal cancer (CRC) 24 . Besides, RPS18 which was related to the recurrence and prognosis of prostate cancer (PCa) was shown to be a potential prognostic biomarker of PCa 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Ribosomal protein S18(RPS18), also known as HKE3, is a type of ribosomal protein which has been supposed to an unfavorable predictor in several cancers including breast cancer (BC) 23 and colorectal cancer (CRC) 24 . Besides, RPS18 which was related to the recurrence and prognosis of prostate cancer (PCa) was shown to be a potential prognostic biomarker of PCa 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified genes with important biological roles for MAC in CRC, such as RPS18 , RPL30 , CXCL9, and IDO1 [ 46 , 47 ]. Machine learning has been applied extensively in biomedicine.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of some authors considering RPL30 as a classical reference gene for cancer research due to its stable expression [ 46 ], our results showed that the overexpression of RPL30 is a hallmark of the dead group in PaCa, being the highest overexpressed gene in this GDC cohort (26.06-fold on average). Likewise, the RPL30 gene has been suggested as one out of eight major genes that predict poor clinical outcomes in mucinous colorectal adenocarcinoma [ 47 ] and is also informative for lethality in medulloblastoma [ 48 ]. In addition, RPL30 is one of seven genes whose expression levels have been proposed for diagnosing prostate cancer [ 49 ].…”
Section: Discussionmentioning
confidence: 99%